Varicella Pneumonia: a Case Report in an Immunocompetent Patient - Heidari, Mahshid; Moghtader Mojdehi, AmirHossein; Babaali, Sahar (Novelty in Biomedicine, 2018)
Background: Varicella (chicken pox) is a highly contagious disease caused by the Varicella-Zoster Virus. Varicella pneumonia is a rare presentation of pneumonia, which is seen in immunocompromised adults. Cases Report: Here we reported a 13-year-old immunocompetent boy who was admitted with fever and acute respiratory symptoms. Conclusion: Varicella pneumonia occurring particularly in immunocompromised patients; however, it should not be misdiagnosed in immunocompetent patients.